Non-planned pregnancy as a risk factor for late start and abandonment of prenatal care - Chilipio-Chiclla, Marco Antonio (2019)
Objectives: Determine if anunplanned pregnancy is a risk factor   for   late-onset   and abandonment  of prenatal  care  in  pregnant  women  served in an I-4  establishment  of  the Social  Security of Peru. Material  and  methods: Observational, retrospective cohort study. Employing probabilistic sampling and simple randomized technique, a sample of 234 pregnant   women   attended in 2017 was selected. An exposed cohort (n=117)  and an unexposed  one  (n=117)  were  formed.  The  Perinatal  Surveillance  System  was  used  as  a secondary information source. Chi-square  test  of  independence  and  relative  risk  (95% confidence interval) were used as a measure of association. Results: Unplanned pregnancy occurred  in  6%  and 15.4% of pregnant and elderly  pregnant  women,  respectively.  Likewise, the primiparity (58.2%), the antecedent of abortion (24.8%) and cesarean section (6.8%)were the  main  reproductive  characteristics  of  the  pregnant  women  whose  pregnancy  was  not planned.  The late start of prenatal care occurred in 51.3% of pregnant women, and the subsequent    abandonment occurred in 15.0% of cases. The anunplanned pregnancy increased  1.48  times  (95%CI:  1.12-1.94;  p=0.004)  the  probabilities  of  starting  prenatal  care late; however, it was not associated with the subsequent abandonment of said prenatal care (p=0.266). Conclusion: Not planning pregnancy slightly raises the  riskof  late  initiation  of prenatal care; however, it is not associated with its subsequent abandonment.